Soil and Ground-water Remediation Techniques - Beck, Raven (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1996)
Summary Urban areas typically contain numerous sites underlain by soils or ground waters which are contaminated to levels that exceed clean-up guidelines and are hazardous to public health. Contamination most commonly results from the disposal, careless use and spillage of chemicals, or the historic importation of contaminated fill on to properties under-going redevelopment. Contaminants of concern in soil and ground water include: inorganic chemicals such as heavy metals, radio active metals, salt and inorganic pesticides, and a range of organic chemicals included within petroleum fuels, coal tar products, PC Boils, chlorinated solvents, and pesti-cides. Dealing with contaminated sitesis a major problem affecting all urbanareas and a wide range of different remedial technologies are available. This chapter reviews the more commonly used methods for ground-water and soil remediation, paying particular regard to efficiency and applicability of specific treatments to different site conditions.